2023
DOI: 10.1002/ldr.4591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation restoration on soil organic carbon in the Loess Plateau: A meta‐analysis

Abstract: Vegetation restoration is one of the most effective ways to increase soil organic carbon (SOC). After the implementation of vegetation restoration policies such as the Grain‐for‐Green Program, which has increased regional vegetation coverage. However, the impact of land use, vegetation types, restoration time, and topographic and meteorological factors on SOC remains unclear. Therefore, this study examined the effect of vegetation restoration on SOC in the Loess Plateau through a meta‐analysis of 520 sample da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The electrochemical behavior of organic matter is related to the development of surface charges and cation exchange capacity [74]. Exploring this relationship further could provide an indirect but cost-effective non-invasive approach to assess the distribution of soil organic matter in restored wetlands, which do not only vary spatially but temporally post-restoration [75].…”
Section: Electrical Conductivity Magnetic Susceptibility and Current ...mentioning
confidence: 99%
“…The electrochemical behavior of organic matter is related to the development of surface charges and cation exchange capacity [74]. Exploring this relationship further could provide an indirect but cost-effective non-invasive approach to assess the distribution of soil organic matter in restored wetlands, which do not only vary spatially but temporally post-restoration [75].…”
Section: Electrical Conductivity Magnetic Susceptibility and Current ...mentioning
confidence: 99%
“…Further, this study integrated restoration time, soil nutrients, and climate to explore their relative contributions to plant taxonomic, functional, and phylogenetic diversity and found that the plant diversity of three dimensions was mainly affected by the coupling effect of restoration time and soil nutrients during the restoration process (Figure 5). The meta-analysis on vegetation ecological restoration conducted by Zhao et al (2023) on the Loess Plateau found that restoration time was the main factor affecting soil organic carbon after vegetation restoration. This suggested that restoration time improved plant diversity in multiple dimensions, mainly by improving soil nutrients.…”
Section: Aerial Seeding Increase Plant Diversity Mainly By Restoring ...mentioning
confidence: 99%
“…Soil C:N:P stoichiometry changes dramatically during forest restoration, which influenced mainly by plant type, mycorrhizal type and climatic zone (Jia et al, 2005; Ouyang et al, 2017; Pan et al, 2021; Song et al, 2019; Zhang et al, 2018). It has been shown that soil C, N and P increased as the succession proceeds (Gao and Huang, 2020; Zhao et al, 2023; Zhou et al, 2017), whereas others showed that total phosphorus (TP) decreased as forest age increased in plantations (Yu et al, 2022; Zhang et al, 2021). Furthermore, forest restoration induced increase in soil C:P and N:P far more than that of C:N, suggesting that forests are primarily limited by P over time (Ouyang et al, 2017; Pan et al, 2021; Zhang et al, 2018; Zhou & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%